Frequency and Duration of Fecal Shedding of Salmonella Enteritidis by Experimentally Infected Laying Hens Housed in Enriched Colony Cages at Different Stocking Densities - Gast, Richard K.; Guraya, Rupa; Jones, Deana R.; Anderson, Kenneth E.; Karcher, Darrin M. (Frontiers in Veterinary Science, 2017)
Human infections with Salmonella Enteritidis are often attributed to the consumption of contaminated eggs, so the prevalence of this pathogen in egg-laying poultry is an important public health risk factor. Numerous and complex environmental influences on Salmonella persistence and transmission are exerted by management practices and housing facilities used in commercial egg production. In recent years, the animal welfare implications of poultry housing systems have guided the development of alternatives to traditional cage-based housing, but their food safety consequences are not yet fully understood. The present study assessed the effects of different bird stocking densities on the frequency and duration of fecal shedding of S. Enteritidis in groups of experimentally infected laying hens housed in colony cages enriched with perching and nesting areas. In two trials, groups of laying hens were distributed at two stocking densities (648 and 973 cm2/bird) into enriched colony cages and (along with a group housed in conventional cages at 648 cm2/bird) orally inoculated with doses of 1.0 × 108 cfu of S. Enteritidis. At 10 weekly postinoculation intervals, samples of voided feces were collected from beneath each cage and cultured to detect S. Enteritidis. Fecal shedding of S. Enteritidis was detected for up to 10 weeks postinoculation by hens in all three housing treatment groups. The overall frequency of positive fecal cultures was significantly (P < 0.05) greater from conventional cages than from enriched colony cages (at the lower stocking density) for the total of all sampling dates (45.0 vs. 33.3%) and also for samples collected at 4–9 weeks postinfection. Likewise, the frequency of S. Enteritidis isolation from feces from conventional cages was significantly greater than from enriched colony cages (at the higher hen stocking density) for the sum of all samples (45.0 vs. 36.7%) and at 6 weeks postinoculation. Moreover, the frequency of S. Enteritidis fecal recovery from enriched colony cages at the higher hen stocking was significantly greater than from similar cages at the lower stocking density for all 10 sampling dates combined (39.4 vs. 33.3%). These results suggest that stocking density can affect S. Enteritidis intestinal colonization and fecal shedding in laying hens, but some other difference between conventional and enriched colony cage systems appears to exert an additional influence.